Determinants of employees productivity among employees in the Malaysian banking industry - Omar, Siti Nur Zahirah; Nawi, Nur Anisah; Nor Azli, Nur Khairunnisa Afrina; Mohd Zaki, Nur Afiqah Wirdani; Adzhari, Nurul Ain; Shamsul, Nur Fatehah (Journal of Islamic, Social, Economics and Development, 2026)
Employee productivity is a key factor influencing organizational performance, particularly in the Malaysian banking industry, where rapid technological advancement, increasing customer expectations, and a highly competitive business environment require employees to perform efficiently and effectively. This study examined the determinants of employee productivity among employees in the Malaysian banking industry by focusing on work environment, employee engagement, job security, training and development, and technological advancement. A quantitative research approach was adopted, and data were collected using structured questionnaires distributed to employees in the Malaysian banking industry. A total of 384 respondents were selected using convenience sampling based on the Krejcie and Morgan sample size determination table. The data collected were analyzed using the Statistical Package for the Social Sciences (SPSS), employing descriptive analysis, Pearson correlation analysis, and simple linear regression analysis. The findings revealed that work environment, employee engagement, job security, training and development, and technological advancement had significantly positive relationships with employee productivity. The study provides valuable insights for banking institutions in developing effective human resource management strategies to enhance employee productivity, improve organizational performance, and strengthen long-term competitiveness within the Malaysian banking industry.